The shadow of childhood harm behind prison walls: theory, evidence, and treatment - Wolff, Nancy L. (Oxford University Press, 2023)
"Criminal. As you read the word 'criminal,' what were the first thoughts that came to your mind? What were the first feelings? When I do this exercise as part of trainings and college classes, the words typically prompted by these questions are: dangerous, scared, selfish, liar, thief, rapist, murderer, violence, drug dealer, guns, psycho, deranged, and many other fear-based and stigmatizing words. These reflexive and stereotypical word impressions of criminals are nourished daily by the news media, social media, and entertainment industry. Movies like Zodiac, The Texas Chainsaw Massacre, and Hannibal, combined with long-running crime drama television series like Criminal Minds and Law and Order and the endless list of top-selling crime novels pushed out annually, summon, reinforce, and sensationalize the presumed evil nature of those who commit crimes. And, once the master label of criminal is attached to a person, all other identities fade into obscurity. Lost are the more humanizing labels of son, daughter, brother, sister, mom, dad, husband, wife, employee, friend, student, citizen, taxpayer, volunteer, and, most of all, person. People who commit a crime, with rare exception, are forever, like Jean Valjean in Victor Hugo's novel Les Misérables, branded by their crime and, ultimately, become one with their crime in our minds and in our public policies that guide and inform prosecution, sentencing, and penal practices"--